Current Advances on the Assessment and Mitigation of Fire Risk in Buildings and Urban Areas—First Edition - Tiago Miguel Ferreira (Fire, 2023)
Fire safety within residential buildings and urban environments continues to be a pressing global concern, demanding dynamic and comprehensive strategies for effective risk assessment and mitigation [...]